Respiratory toxicity and immunotoxicity evaluations of microparticle and nanoparticle C60 fullerene aggregates in mice and rats following nose-only inhalation for 13 weeks. Issue 10 (25th November 2016) - Sayers, Brian C.; Germolec, Dori R.; Walker, Nigel J.; Shipkowski, Kelly A.; Stout, Matthew D.; Cesta, Mark F.; Roycroft, Joseph H.; White, Kimber L.; Baker, Gregory L.; Dill, Jeffrey A.; Smith, Matthew J.
Abstract: C60 fullerene (C60), or buckminsterfullerene, is a spherical arrangement of 60 carbon atoms, having a diameter of approximately 1 nm, and is produced naturally as a by-product of combustion. Due to its small size, C60 has attracted much attention for use in a variety of applications; however, insufficient information is available regarding its toxicological effects. The effects on respiratory toxicity and immunotoxicity of C60 aggregates (50 nm [nano-C60] and 1 μm [micro-C60] diameter) were examined in B6C3F1/N mice and Wistar Han rats after nose-only inhalation for 13 weeks. Exposure concentrations were selected to allow for data evaluations using both mass-based and particle surface area-based exposure metrics. Nano-C60 exposure levels selected were 0.5 and 2 mg/m 3 (0.033 and 0.112 m 2 /m 3 ), while micro-C60 exposures were 2, 15 and 30 mg/m 3 (0.011, 0.084 and 0.167 m 2 /m 3 ). There were no systemic effects on innate, cell-mediated, or humoral immune function. Pulmonary inflammatory responses (histiocytic infiltration, macrophage pigmentation, chronic inflammation) were concentration-dependent and corresponded to increases in monocyte chemoattractant protein (MCP)-1 (rats) and macrophage inflammatory protein (MIP)-1α (mice) in bronchoalveolar lavage (BAL) fluid. Lung overload may have contributed to the pulmonary inflammatory responses observed following nano-C60 exposure at 2 mg/m 3 and micro-C60 exposure at 30 mg/m 3 . Phenotype shifts in cells recovered from the BAL were also observed in all C60-exposed rats, regardless of the level of exposure. Overall, more severe pulmonary effects were observed for nano-C60 than for micro-C60 for mass-based exposure comparisons. However, for surface-area-based exposures, more severe pulmonary effects were observed for micro-C60 than for nano-C60, highlighting the importance of dosimetry when evaluating toxicity between nano- and microparticles.